Sleep quality, chronotype, temperament and bipolar features as predictors of depressive symptoms among medical students. (3rd July 2017) - Mokros, Łukasz; Witusik, Andrzej; Michalska, Julia; Łężak, Wojciech; Panek, Michał; Nowakowska-Domagała, Katarzyna; Antczak, Adam; Pietras, Tadeusz
ABSTRACT: The assessment of risk factors is a crucial step in the prevention and treatment of affective disorders and should encompass personal dispositions. The aim of this study was to assess the value of chronotype and temperament as independent predictors of depressive symptoms among medical students. The study surveyed 140 students of the Faculty of Medicine with a battery of questionnaires: the Beck Depression Index (BDI), Hypomania Checklist 32 (HCL-32), Pittsburgh Sleep Quality Index (PSQI), Chronotype Questionnaire and Eysenck Personality Questionnaire Revised. The results were tested using Pearson's correlation quotient and general linear model. Ten percent of the participants demonstrated a BDI score suggestive of clinically significant depressive symptoms. BDI score correlated positively with HCL-32 score. A rise in BDI was independently predicted by elevated Neuroticism and PSQI scores and morningness. Those effects were independent from each other and from other parameters of the model. The presence of depressive symptoms might be associated with bipolar features among medical students. Poor sleep quality predicted depressive symptoms, similarly to Neuroticism and independently of temperament and chronotype. Future studies on the associations between personal dispositions and mood disorders among medical students are required to help identify those at greater risk of developing affective illness. Effective prophylaxis and early intervention are warranted to ensure better treatment results.